Ofatumumab successfully treats myelin oligodendrocyte glycoprotein antibody-associated disease accompanied by Epstein-Barr viral infection: a case series - Min, Chen; Zhuajin, Bi; Peidong, Liu; Ruoyu, Li; Ju, Liu; Hongbo, Liu (Frontiers in Immunology, 2025)
Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) caused by pathogenic immunoglobulin G antibodies to myelin oligodendrocyte glycoprotein is a rare demyelinating disease of the central nerve system (CNS). The clinical phenotypes of MOGAD include acute disseminated encephalomyelitis, optic neuritis, and transverse myelitis. At present, the mechanism underlying the disease is unknown. Herein, we report two cases of MOGAD accompanied by Epstein-Barr virus (EBV) infection. Both presented inflammation response in the cerebrospinal fluid (CSF), demonstrating elevated level of cell accounts and protein. EBV genomic sequence was also detected in the CSF samples. The patients recovered substantially after 3 months following a combination treatment with methylprednisolone and immunosuppressive therapy with ofatumumab. These cases provide new insight into the production of MOG-IgG and the possible pathological mechanisms underlying MOGAD. The cases also confirm the association with EBV, a virus that infects human B cells and has been proposed to be a trigger for MOGAD. This is the first report on subcutaneous ofatumumab treatment for MOGAD triggered by EBV, suggesting that this is a potentially valuable therapeutic option.